Pengelolaan Informasi Privat dan Mitigasi Risiko Sosial pada Mahasiswa Kos Pelaku Perilaku Seksual Pranikah di Kota Madiun - Neni Utami Ardianingsih; Maria Magdalena; Fikri Hasan (Universitas Tribhuwana Tungga Dewi, 2026)
This study explores the privacy communication management of boarding house students in Madiun engaged in premarital sexual behavior through the lens of Communication Privacy Management (CPM). Using a qualitative case study approach, the research focuses on how these individuals manage information ownership, construct privacy boundaries, and navigate turbulence within interpersonal relationships. Data were gathered through in-depth interviews with three students and analyzed using CPM’s core pillars: privacy ownership, boundaries, rules, and turbulence. The findings reveal that students perceive their sexual behavior as highly sensitive private property under their absolute control as information owners. Disclosure is executed selectively, dictated by levels of interpersonal trust, relationship context, and potential social risks. Consequently, students establish situational and flexible privacy rules while designating specific confidants as